Historical style : fashion and the new mode of history, 1740-1830 - Campbell, Timothy, 1978- (Material texts., 2016)
In Historical Style, Timothy Campbell argues that the eighteenth-century fashion press shaped British perception of time and history by producing new curiosity about the very recent past and a new self-consciousness about the means by which the past could be understood.